2019
DOI: 10.3390/ijms20133196
|View full text |Cite
|
Sign up to set email alerts
|

Dark Antibacterial Activity of Rose Bengal

Abstract: The global spread of bacterial resistance to antibiotics promotes a search for alternative approaches to eradication of pathogenic bacteria. One alternative is using photosensitizers for inhibition of Gram-positive and Gram-negative bacteria under illumination. Due to low penetration of visible light into tissues, applications of photosensitizers are currently limited to treatment of superficial local infections. Excitation of photosensitizers in the dark can be applied to overcome this problem. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 45 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Rose Bengal is an organic anion dye that has been clinically used for decades and has been used to assess eye surface epithelium damage of eye surface disease 38 . Also, it is a water-soluble photosensitiser with a distinctive wine colour 39 . It is well known that singlet-oxygen production of Rose Bengal after exposure with 300-600 nm radiation increases the antibacterial effect [40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…Rose Bengal is an organic anion dye that has been clinically used for decades and has been used to assess eye surface epithelium damage of eye surface disease 38 . Also, it is a water-soluble photosensitiser with a distinctive wine colour 39 . It is well known that singlet-oxygen production of Rose Bengal after exposure with 300-600 nm radiation increases the antibacterial effect [40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…The term sonodynamic antimicrobial chemotherapy (SACT) refers to the application of this strategy to kill microorganisms. [3,[100][101][102][103] As in photodynamic treatment, sonodynamic treatment is based on the combined action of three components: US, sensitizer, and molecular oxygen. Some molecules exhibiting photodynamic activity produce free radicals when irradiated with US.…”
Section: Sonodynamic Antimicrobial Chemotherapymentioning
confidence: 99%
“…In our later studies, Rose Bengal was immobilized onto silicone, and in this case the Rose Bengal also showed significant antibacterial activity against S. aureus in the dark under ultrasonic activation, probably due to Rose Bengal leaching from the polymer during ultrasonic treatment. [102] Since Rose Bengal possesses both photo-and US-sensitive properties, it has been the subject of scientific attention. [107] Costley et al demonstrated the sonodynamic antibacterial activity of Rose Bengal when conjugated to an antimicrobial peptide KLAKLAK against planktonic cultures of S. aureus and P. aeruginosa, as well as P. aeruginosa biofilms, and in vitro and in vivo mouse models.…”
Section: Sonodynamic Antimicrobial Chemotherapymentioning
confidence: 99%
“…Then, the acceleration of enzyme activity by adding a small amount Rose Bengal is a water-soluble photosensitizer [28] producing singlet oxygen after exposure to 300-600 nm radiation. [29] Its antibacterial and anticancer activities have been clinically applied to various diseases.…”
Section: P Aeruginosa Displaying a Competitive Inhibitory Fashion Of Rosementioning
confidence: 99%